Transaction Management in Homogenous Distributed Real-Time Grid Database Systems - Ratawa, Surya Prakash (IJRDO -Journal of Computer Science Engineering, 2017)
Distributed processing systems incorporating fully replicated databases are inherently more reliablethan systems having partitioned and partially replicated databases. Since every site has a complete copy of thedatabase, greater system functional integrity is provided in the event of network partitions. A network partitioncan occur when a break occurs in the communication medium isolating one or more processor sites. In addition tothe greater reliability, there is a reduction in the associated control required. There is no need for the complicatedmechanisms for maintaining owners (the primary data copy) and an acceptable number of subscriber copies(secondary copies or replications) of each database partition. There is also an improvement in performanceobtainable from the use of local copies of data at each site. Faster access memory systems and higher speedcommunications improve performance of both partially and fully replicated database systems. However, potentialimprovements in performance can only be achieved by using update algorithms which require significantly lessinter-site communication. An example of a homogeneous distributed processing system architecture incorporatinga fully replicated database system. A homogenous distributed real time replicated database system is a network oftwo or more DBMS that reside on one or more machines. A distributed system that connects two or moredatabases are Homogenous Distributed Database Systems (HDDBS) create different problems when accessingdistributed and replicated databases. Particularly, access control and transaction management in HDDBS requiredifferent mechanism to monitor data retrieval and update to databases. Current trends in multi-tier client/servernetworks make DDBS an appropriated solution to provide access to and control over localized databases. Thispaper highlights the basic concepts underlying distributed database system including transaction management inin HDRTDBS.